Sample introduction in multi-syringe flow injection systems: comparison between time-based and volume-based strategies - Segundo, Marcela A. (2010)
In multi-syringe flowinjection analysis (MSFIA), devices as selection, injection or commutation valves must be incorporated to the manifold to provide access to sample and standard solutions. Therefore, the definition of sample amount can be either volume or time-based. In the present work, four configurations for sample introduction (two for each approach) were tested in order to establish if the different strategies affect the analytical signal in MSFIA systems. The mean absorbance value from ten consecutive injections of a bromothymol blue solution obtained for the time-based strategy was lower than that provided by the volume-based approach as the exact volume delivered by each configuration was different from the “theoretical” volume. For time-based configurations, the exact volume delivered is 2–5% lower than the theoretical value while for volume-based configurations, the volume delivered was between 6 and 46% larger than the theoretical volume. Moreover, for time-based sampling, the order of steps in the analytical cycle was of utmost importance since any alteration in the flow direction affected the volume delivered in the subsequent step in the analytical cycle. The influence of the two sampling approaches was also evaluated in the MSFIA systems for the spectrophotometric determination of phenolic compounds and the potentiometric determination of chloride. There was no evidence that the use of either volume or time-based sampling would improve the analytical features of these determinations when real samples were tested.